2016
DOI: 10.1007/s00415-016-8312-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in IBA57 are associated with leukodystrophy and variable clinical phenotypes

Abstract: Defects of the Fe/S cluster biosynthesis represent a subgroup of diseases affecting the mitochondrial energy metabolism. In the last years, mutations in four genes (NFU1, BOLA3, ISCA2 and IBA57) have been related to a new group of multiple mitochondrial dysfunction syndromes characterized by lactic acidosis, hyperglycinemia, multiple defects of the respiratory chain complexes, and impairment of four lipoic acid-dependent enzymes: α-ketoglutarate dehydrogenase complex, pyruvic dehydrogenase, branched-chain α-ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 30 publications
2
60
1
Order By: Relevance
“…IBA57 mutations in 11 patients MRI features in patients with IBA57 mutations MRI features varied among the different phenotypes. Lesions in thalamus and cervical spinal cord were described in a previously reported case 6. In the acute/subacute phase, lesions commonly involved the periventricular/central WM of the frontal and parieto-occipital lobes, the corpus callosum, and the temporal WM.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…IBA57 mutations in 11 patients MRI features in patients with IBA57 mutations MRI features varied among the different phenotypes. Lesions in thalamus and cervical spinal cord were described in a previously reported case 6. In the acute/subacute phase, lesions commonly involved the periventricular/central WM of the frontal and parieto-occipital lobes, the corpus callosum, and the temporal WM.…”
mentioning
confidence: 80%
“…The lesion extent score was 6.7 (4)(5)(6)(7)(8)(9)(10)(11) in the peak phase and 8.3 (6)(7)(8)(9)(10) in the recovery phase (Z = −1.06, P = .35). The lesion extent score was 6.7 (4)(5)(6)(7)(8)(9)(10)(11) in the peak phase and 8.3 (6)(7)(8)(9)(10) in the recovery phase (Z = −1.06, P = .35).…”
Section: Extent Of Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study using a mouse model suggested that only ISCA1 is required for the maturation of mitochondrial [4Fe-4S] clusters [ 43 ]. Defects in ISCA1, ISCA2 and IBA57 have been associated with numerous mitochondrial diseases now categorized as multiple mitochondrial dysfunctions syndromes MMDS3 (IBA57) [ 80 , 81 , 187 ], MMDS4 (ISCA2) [ 79 ], and MMDS5 (ISCA1) [ 77 , 78 ]. A common phenotype of these MMDS diseases is the deficiency in mitochondrial [4Fe-4S] proteins, such as lipoic acid synthase (LAS), a strong indication of their functions in mitochondrial [4Fe-4S] cluster maturation.…”
Section: Maturation Of [4fe-4s] Cluster By Nmrmentioning
confidence: 99%